Dietary fat and cardiometabolic health: evidence, controversies, and consensus for guidance. (13th June 2018) - Forouhi, Nita G; Krauss, Ronald M; Taubes, Gary; Willett, Walter
Abstract : Although difficulties in nutrition research and formulating guidelines fuel ongoing debate, the complexities of dietary fats and overall diet are becoming better understood, argue Nita G Forouhi and colleagues